The relationship between variables of the internal work environment and the work pressures in the organization - Dahan, Mohamed; Koraychi, Hajer (Milev Journal of Research and Studies, 2017)
The internal work environment and its components have always been a determining factor in the success of the company, Since the performance of human resources could be influenced either positively or negatively by the effect of these components. Indeed, the main constituents of this environment, which are The post itself, Work systems and procedures, Leadership, physical and social work environment ... etc, Can be factors of satisfaction and stimulation for workers, as they can become a source of pressures and tensions that create psychological, social, and economic problems for workers and the organization to which they belong.